Fiber-reinforced composites materials, manufacturing and design - Mallick , P. K (Mechanical engineering (Marcel Dekker, Inc.), 1993)
Maintaining the interdisciplinary perspective of the first edition, this reference and text provides comprehensive discussions of all aspects of fiber-reinforced composites, including materials, mechanics, properties, test methods, manufacturing and design. Written from a conceptual point of view and emphasizing fundamentals, the second edition of Fiber Reinforced Composites offers updated and expanded sections including: fibers and matrix, including thermoplastic matrices; discontinuous fibers and laminated structures; static mechanical properties, fatigue properties and damage tolerance; resin flow, bag molding, filament winding and resin transfer molding; and environmental effects.